Acceptability in The Serial Cartoon Film Entitled Carl Transform into Carl Dadi (English-Javanese Translation) - Ika Oktaria Cahyaningrum (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Translation in entertainment’s media has a very big role, especially in media that is often seen by many viewers, one of them is the cartoon series through the YouTube channel entitled “Carl Transform”. This film series has many fans, especially children. The Carl Transform series in English has also been translated into various languages, especially is Indonesian. Not only in Indonesian translation but also this film series has also been translated into Javanese and the title has changed to “Carl Dadi”. This research uses the object of the Carl Transform film series with a discussion focused on acceptability of English into Javanese. This research is included in a qualitative descriptive study, which describes and explains in detail how the quality of acceptance is produced in the Javanese version. In purposes that the audience can find out the level of acceptance generated in the target language, and know the new terms found in Javanese.